Controllability of nonlinear Volterra integrodifferential systems with prescribed controls. (1992) - Balachandran, K.; Lalitha, D.
Abstract : Sufficient conditions for the global controllability of nonlinear Volterra integrodifferential systems with prescribed controls are derived. The method is a transformation of the given control system into a boundary value problem and then the result is obtained by the application of the Schaefer fixed point theorem.